Management Essential Hypertension in Elderly Patients at Primary Health Centers : A Systematic Review - Anisa Septa Rini (International Medical Journal Corp. Ltd, 2026)
Introduction: Managing essential hypertension in elderly patients (≥65 years) in primary care is challenging due to multimorbidity, polypharmacy, and limited evidence on optimal strategies. This systematic review evaluates the effectiveness of various management interventions. Methods: We screened 80 included sources (RCTs, etc) from primary care settings. Interventions included pharmacological strategies, deprescribing, pharmaceutical care, digital health (telemonitoring, mHealth), community-based programs, educational/behavioral models, and complementary therapies. Primary outcomes were blood pressure (BP) reduction and control rates; secondary outcomes included medication adherence and safety. Results: Significant positive findings include: (1) Pharmacological: ACP/AAFP guideline showed SBP <150 mmHg reduces stroke (RR 0.77) and cardiac events (RR 0.83) (1). HYVET trial in ≥80 years reduced total mortality (HR 0.48) (2). (2) Deprescribing: OPTIMISE trial demonstrated non-inferiority of medication reduction, maintaining SBP <150 mmHg in 86.4% (3). (3) Pharmaceutical care: 36-month program achieved SBP reduction -23.0 mmHg (11). (4) Community KAP model improved BP control from 20.4% to 74.4% (25). (5) Digital interventions: telemonitoring increased control to 71.3% vs 49.8% (12); WeChat-based intervention reduced SBP -7.36 mmHg (56). (6) Physical activity: walking interventions reduced SBP by -7.0 to -8.7 mmHg (5,6). (7) Complementary therapies in Indonesian studies: self-acupressure (-18.05 mmHg) (20), back massage (-15.5 mmHg) (29), DASH diet education (-18.5 mmHg) (23). Medication adherence improved significantly with pharmacist-led programs (96.9% adherence) (9) and peer education (MMAS-8 7.33±0.41) (76). Discussion: Heterogeneity is explained by population stratification, intervention intensity, and study design. Intensive treatment benefits frail elderly, while deprescribing is safe in well-controlled patients. Technology works best with active feedback. Conclusion: Multifaceted, team-based interventions (pharmacist-led, community health worker-delivered, with telemonitoring feedback) produce significant, sustained BP reduction and adherence improvement in elderly primary care patients.